Mycobacterium marinum persists in cultured mammalian cells in a temperature-restricted fashion. - Ramakrishnan, L (1994)
We have explored the relatively rapidly growing animal and human pathogen Mycobacterium marinum as an experimental model for mycobacterial pathogenesis. M. marinum, which has a lower temperature for optimal growth than does Mycobacterium tuberculosis, has a much shorter generation time and can be safely studied in ordinary laboratory facilities and examined in multiple animal infection models. We have established an in vitro assay for its interaction with eukaryotic cells and shown that it persists in these cells in a temperature-specific fashion that correlates with its ability to cause disease in vivo at lower temperatures. Additionally, preliminary evidence that M. marinum causes a chronic disease with some features resembling tuberculosis in frogs of the species Rana pipiens is presented.